OF THE DEAR DICTIONARIES. ON THE SPECIAL LEXICOGRAPHY OF GERMAN IN ROMANIA – AN ENCOURAGING REVIEW (Analele Universităţii Bucureşti. Limbi şi Literaturi Străine, 2024)
Starting from some considerations about the historic language usus, the article presents the status and the peculiarities of Romanian German. Statements regarding the current linguistic status of the German language in Romania and its speakers are being made with regard to the present linguistic context, aiming to highlight the profile of German as a regional language and to point out the need for its lexicographic charting in specialised dictionaries.
Keywords: regional German language; Transsylvanian-Saxon; Romanian German; specialized lexicography; dialect